Social distance and trust: experimental evidence from a slum in Cairo - Binzel, Christine; Fehr, Dietmar (Journal of development economics, 2013)
While strong social ties help individuals cope with missing institutions, trade is essentially limited to those who are part of the social network. We examine what makes the decision to trust a stranger different from the decision to trust a member of a given social network (a friend), by comparing the determinants of these two decisions for the same individual. We implement a binary trust game with hidden action in a lab-in-the-field experiment with residents of an informal housing area in Cairo. Our results show that trust is higher among friends than among strangers and that higher trust among friends is related to the principal's belief of trustworthiness. However, on average a principal underestimates her friend's trustworthiness leading to inefficient outcomes. Our findings suggest that even within a social network, trade may often be limited to exchanges with few information asymmetries.
Gesehen am 26.11.2020